COVID-19 and autism (2020)
The current pandemic of Covid-19 has created a paradigm for possibly gaining greater insight in two conditions: 1) Inflammatory maladies in pregnancy, and. 2) The biology of IGF-1 in autism. Studies since the beginning of this century have supported the view that IGF-1 deficiency in the neonate defines the basis of autism. As a result, it appears that interleukin-6 in corona virus-based infections causes reduced defenses because of suppressed IGF-1, especially in older patients. This may also portend an increase of autism in the offspring of gravidas currently affected severely by Covid-19.